Kebijakan Pendidikan Karakter Dalam Meminimalisir Kenakalan Remaja - Farid Setiawan; Wildan Taufiq; Ayu Puji Lestari; Risma Ardianti Restianty; Lailli Irna Sari (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2021)
The role of character education in shaping student character is as a counterweight to cognitive skills for students. The implementation of character education itself has been reflected in Rasullullah SAW. In the person of the Apostle who contains great and noble values. Therefore the important role of teachers, school principals, and parents in building the character of students is needed. Teachers and parents must collaborate in instilling the character values of students so that later the character education received by children will be in accordance with what must be taught. Cultivating character education is very important for students so that in the future they can find out how good deeds are done and not good to use. Juvenile delinquency at this time is triggered because of being influenced by the circle of friends he follows, which causes them to be easily influenced by invitation from friends who they think are appropriate examples. This research was conducted to analyze the character education policy in minimizing juvenile delinquency.